USE OF AN INDUCTION MACHINE FOR THE GENERATOR OPERATING MODE IN A SMALL HYDRO POWER PLANT - Blaznik, Matic; Hadžiselimović, Miralem; Štumberger, Bojan; Zagradišnik, Ivan (Journal of Energy Technology, 2024)
Rising demands for energy and the closure of nuclear power plants in many countries has rapidly increased the importance of harvesting energy from unconventional power sources. Small hydro power represents one of the cleanest and most frequently used renewable sources of power all over the world. Renewable energy is connected with reducing emissions and costs; therefore, the use of small rivers and streams plays a major role. Because of the many advantages that an induction machine provides, the use of an induction motor as a generator is the most suitable solution for small hydro applications. The aim of this paper is to present a practical approach for the use of an induction motor as a generator. Moreover, the operating modes of an induction machine are explained and supported with experimental measurements and calculations with the emLook motor design software.